Spatiotemporal distribution and ecological factors of disease burden in Inner Mongolia’s working age population with brucellosis from 2015 to 2020 - Yu, Lei; Zheng, Huiqiu; Wang, Yanling; Wang, Xinyan; Wang, Xuemei (Scientific reports, 2025)
Brucellosis is a major public health problem globally, with cases concentrated in working-age populations, but there are few studies on the disease burden of brucellosis in working-age populations. This study estimated the disease burden and spatiotemporal distribution characteristics of brucellosis in Inner Mongolia’s working-age population from 2015 to 2020 and explored the ecological influences on its disease burden. Spatiotemporal Bayesian modeling was utilized; thus, the spatiotemporal variation pattern of disease burden of brucellosis was analyzed. Using the geographically weighted regression analysis (GWR), the study explored the ecological influencing factors of the burden of brucellosis in the working-age population. Bayan Nur in Inner Mongolia exhibited a low risk of disease burden of brucellosis, but the risk of disease burden of brucellosis has fast increasing speed from 2015 to 2020 there. A considerably high number of slaughtered fattened sheep and goats (β: 0.008734–0.008752, P < 0.05), number of health beds (β: − 0.005591 to 0.005579, P < 0.05), and high rainfall (β: 0.015433–0.015439, P < 0.05) are ecological influences on the disease burden of brucellosis in the working-age population of Inner Mongolia. In the prevention and control of brucellosis, the goverment commonly focus on regions with a high disease burden, and it is equally important which those regions where the increase of disease burden is fast but its disease burden is not high. High number of slaughtered fattened sheep and goats, high rainfall, and a low number of health beds are ecological influences on the disease burden of brucellosis among the working-age population. Combined with our ecological influencing factors, we can take prevention and control measures in advance for the working-age population in areas with a fast rising rate of the disease burden of brucellosis.